EXAMINATION OF DIFFERENT MODELS OF TROPOSPHERE DELAYS IN SBAS POSITIONING IN AERIAL NAVIGATION - Kamil KRASUSKI; Małgorzata KIRSCHENSTEIN (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents the results of a study on the use of different tropospheric correction models in SBAS positioning for air navigation. The paper, in particular, determines the influence of the Saastamoinen troposphere and RTCA-MOPS models on the determination of aircraft coordinates and mean coordinate errors in the SBAS positioning method. The study uses real kinematic data from a GPS navigation system recorded by an onboard GNSS satellite receiver as well as SBAS corrections. In the experiment, the authors include SBAS corrections from EGNOS and SDCM augmentation systems. The navigation calculations were performed using RTKLIB v.2.4.3 and Scilab 6.1.1 software. Based on the conducted research, it was found that the difference in aircraft coordinates using different troposphere models can reach up to ±2.14 m. Furthermore, the use of the RTCA-MOPS troposphere model improved the values of mean coordinate errors from 5 to 9% for the GPS+EGNOS solution and from 7 to 12% for the GPS+SDCM solution, respectively. The obtained computational findings confirm the validity of using the RTCA-MOPS troposphere model for SBAS positioning in aerial navigation.